STRATEGY FOR IMPROVING THE ECONOMY OF COASTAL FAMILIES IN SERDANG BEDAGAI REGENCY BASED ON ECOPRENEURSHIP - Willy Cahyadi; Bobby Hartanto; Dedy Dwi Arseto (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The aim of this research is to provide an effective strategy for improving the economy of coastal families in Serdang Bedagai Regency. Serdang Bedagai Regency has great potential in coastal natural resources, but many coastal families still face economic constraints with monthly incomes below 2.5 million rupiah. Many of them even have to work outside the area to meet their daily needs. An ecopreneurship-based economic improvement strategy is a relevant solution to overcome this challenge. This includes education, training and development of sustainable, ecologically based businesses. Collaboration with related agencies, non-governmental organizations, NGOs and educational institutions is also needed to support the implementation of this strategy. Through this ecopreneurship approach, it is hoped that coastal families in Serdang Bedagai Regency can increase their income while preserving natural resources that are important for their lives and those of future generations, as well as encouraging sustainable economic growth in the region.